EVALUATING THE OPERATIONAL AND THE ENVIRONMENTAL BENEFITS OF A SMART ROUNDABOUT - Alkhaledi, Khaled Ali (The South African Journal of Industrial Engineering, 2015)
Vehicle fuel consumption and emission rates in Kuwait have increased considerably over recent decades, and are now causing health and economic problems. A three-lane smart roundabout is a new and innovative design idea that can help to mitigate these issues. The smart roundabout was designed with a dedicated exit lane on the right side of each entryway, and a U-turn path connecting each adjacent entry and exit road. Both features permit vehicles to turn in specific directions without needing to enter the roundabout itself. Underground tunnels were designed for pedestrian and cyclist use. The objective of this study was to measure the impact of a smart roundabout on vehicle fuel consumption and on emissions of carbon dioxide, carbon monoxide, nitrogen oxides, and hydrocarbons. These results were then compared with those of a traditional roundabout and of a light-signalised intersection. Two light-signalised intersections with different traffic volumes were chosen for this study and simulated in their present state, as replaced by traditional roundabouts; and as replaced by smart roundabouts using the SIDRA 6.0 software. The smart roundabout allowed traffic to proceed with minimal delay and idling time, significantly reducing vehicle fuel consumption and emissions in comparison with a traditional roundabout or light-signalised intersection. Furthermore, the smart roundabout allowed pedestrians and cyclists to move safely through the intersection without interacting with vehicular traffic